Application of the Checkerboard Immunoblotting Technique to the Quantification of Host Biomarkers in Gingival Crevicular Fluid - Teles, Ricardo P.; Sakellari, Dimitra; Konstantinidis, Antonis; Socransky, Sigmund S.; Haffajee, Anne D. (Journal of periodontology (1970), 2009)
Background: The aim of this study was to describe the development and validation of the checkerboard immunoblotting (CBIB) technique for the high‐throughput quantification of multiple inflammatory mediators in gingival crevicular fluid (GCF) samples. Methods: Monoclonal antibodies were used to bind GCF interleukin (IL)‐1β and −8 and matrix metalloproteinase (MMP)‐8 to the surface of membranes. Biotinylated antibodies were used to detect bound antigens in a checkerboard format. Signals were developed using chemiluminescence, captured on film, and quantified using software for array analysis. The assay was tested for potential cross‐reactions among the three pairs of antibodies. Eleven CBIBs were processed to determine the analytical sensitivity of the assay. Forty GCF samples were analyzed using CBIB and enzyme‐linked immunosorbent assay (ELISA) in parallel, and the significance of the correlations among the results was tested using the Pearson correlation coefficient. Nine hundred thirty‐one GCF samples were collected from 20 periodontally healthy subjects and 20 periodontitis subjects and analyzed using CBIB to test the assay's sensitivity and dynamic ranges using clinical samples. Results: The CBIB was capable of distinguishing among the three analytes. The sensitivity and dynamic ranges of the assay were suitable for the detection of the three targets in the majority of GCF samples. There were highly statistically significant (P <0.0001) positive correlations between CBIB and ELISA data for all three biomarkers. The periodontitis subjects had statistically significantly higher mean levels of IL‐1β and −8 compared to healthy subjects. Conclusion: The CBIB technique is a sensitive and specific assay for the high‐throughput quantification of MMP‐8 and IL‐8 and −1β in GCF.